Trading behaviour and return performance of speculators and hedgers : currency and precious-metal futures 1992 - 2003 - Jeenath Mehron Mohd Yahaya (2008)
This paper investigates the trading behaviour and return performance of hedgers and speculators in eight currency and four precious metal futures contracts.For the investigation, we construct weekly data on futures returns, three pricing factors, and major traders’ net futures positions for the period from October 1992 to November 2003.